Persepsi Guru Terhadap Kegiatan Supervisi Akademik Oleh Kepala Sekolah Di SMA Negeri Se Kecamatan Pasaman Kabupaten Pasaman Barat - Tika; Adi, Nelfia; Anisah; Alkadri, Hanif (Global Action and Education for Society, 2023)
The research aims to obtain information regarding teachers perceptions of planning, implementation,assessment and feedback activities for academic supervision by school principals in stage high school in Pasaman District, Pasaman Regency. The type of research used is quantitative descriptive. The population in this study were all teachers at SMA N 1 and SMA N 2 Pasaman, namely 107 teachers and the sample was 50 teachers ( SMA N 1 ) and 57 Teachers ( SMA N 2 ) using the proportional random sampling method the instrument in this research uses a likert scale questionnaire which has been tested for validity and reliability. The data analysis used is descriptive statistical analysis method. The result of this research are 1 ) planning obtained 4,45 in the good category, 2) implementation obtained 4,56 in the good category, 3) assessment obtained 4,6 in the very good category, and 4) feedback obtained 4,31 in the good category.